The Ways to Die: Cell Death in Liver Pathophysiology - Cao, Peng; Jaeschke, Hartmut; Ni, Hong-Min; Ding, Wen-Xing (Seminars in Liver Disease, 2025)
Liver diseases are closely associated with various cell death mechanisms, including apoptosis, necroptosis, autophagy, pyroptosis, and ferroptosis. Each process contributes uniquely to the pathophysiology of liver injury and repair. Importantly, these mechanisms are not limited to hepatocytes; they also significantly involve nonparenchymal cells. This review examines the molecular pathways and regulatory mechanisms underlying these forms of cell death in hepatocytes, emphasizing their roles in several liver diseases, such as ischemia–reperfusion injury, metabolic dysfunction-associated steatotic liver disease, drug-induced liver injury, and alcohol-associated liver disease. Recent insights into ferroptosis and pyroptosis may reveal novel therapeutic targets for managing liver diseases. This review aims to provide a comprehensive overview of these cell death mechanisms in the context of liver diseases, detailing their molecular signaling pathways and implications for potential treatment strategies.
Keywords: apoptosis; autophagy; ferroptosis; necroptosis; pyropotsis